Sustainable Global Supply Chains for Cafés and Bars : Fair Trade and Eco-Labels - Romanov, Artem (2025)
This thesis explores integrating sustainability practices into global supply chains within the café and bar industry, focusing on Fair Trade and eco-label certifications. It examines how these certifications impact economic performance, environmental responsibility, and social equity across various supply chain stages. Drawing on a mixed-methods approach, the research combines qualitative insights, case studies, and quantitative data to assess the adoption, effectiveness, and challenges of implementing sustainable standards. The analysis highlights significant regional differences, barriers to certification for small businesses, and the role of consumer behavior in driving ethical purchasing. Results indicate that while Fair Trade and eco-labels can enhance brand value and operational resilience, their broader adoption depends on institutional support, cost-efficiency, and increased consumer education. The findings emphasize the need for strategic implementation tailored to local contexts to achieve meaningful progress toward sustainability in the café and bar sector.